Influence of Impregnation and Coprecipitation Method in Preparation of Cu/ZnO Catalyst for Methanol Synthesis - Yusi Prasetyaningsih; Hendriyana Hendriyana; Herri Susanto (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Cu/ZnO catalyst was succesfully prepared using a coprecipitation method. The mixing procedure of the Cu(NO3)2, Zn(NO3)2 and Na2CO3 solutions had an important influence on the characteristics of the catalyst. The best catalyst obtained was the one prepared with slow mixing of the salt solutions and a CuO/ZnO molar ratio of 50:50. This raw catalyst had a maximum surface area of about 61.6 m2/g. Increasing the CuO/ZnO molar ratio caused an agglomeration of precipitated particles, reducing the surface area. A much better catalyst was obtained using an impregnation method, in which g-Al2O3 was used as support. The impregnated catalyst had a surface area of about 151 m2/g. Activity tests were carried out in a fixed-bed reactor containing 1 g of catalyst and a flow of syngas at a rate of 60 mL/min. The reaction temperature was 170°C and the pressure was 20 barg. The best coprecipitated catalyst gave a CO conversion of about 10%, while the impregnated catalyst gave a CO conversion of up to 69%.